2018
DOI: 10.1038/s41598-018-31801-y
|View full text |Cite
|
Sign up to set email alerts
|

Nystatin-like Pseudonocardia polyene B1, a novel disaccharide-containing antifungal heptaene antibiotic

Abstract: Polyene macrolides such as nystatin A1 and amphotericin B belong to a large family of very valuable antifungal polyketide compounds typically produced by soil actinomycetes. Recently, nystatin-like Pseudonocardia polyene (NPP) A1 has been identified as a unique disaccharide-containing tetraene antifungal macrolide produced by Pseudonocardia autotrophica. Despite its significantly increased water solubility and decreased hemolytic activity, its antifungal activity remains limited compared with that of nystatin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…Compared to nystatin A1, NPP A1 displayed a 300-fold increase in water solubility, 10-fold reduced hemolytic activity, but also~50% lower antifungal activity against Candida albicans. The issue of lowered bioactivity was later solved through the manipulation of the ER domain in module five (ER5) of the NPP biosynthetic cluster [312]. Deleting this gene disables the reduction at the C28-C29 unsaturated bond in the aglycone of NPP A1 hence, generating a heptaene instead of the original tetraene.…”
Section: Amphotericin Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to nystatin A1, NPP A1 displayed a 300-fold increase in water solubility, 10-fold reduced hemolytic activity, but also~50% lower antifungal activity against Candida albicans. The issue of lowered bioactivity was later solved through the manipulation of the ER domain in module five (ER5) of the NPP biosynthetic cluster [312]. Deleting this gene disables the reduction at the C28-C29 unsaturated bond in the aglycone of NPP A1 hence, generating a heptaene instead of the original tetraene.…”
Section: Amphotericin Bmentioning
confidence: 99%
“…However, the production yields of NPP B1 in the pathway-engineered strain (P. autotrophica ER5 mutant) were extremely low. In an attempt to solve this issue, the P. autotrophica ER5 mutant strain was subjected to N-methyl-N -nitro-N-nitrosoguanidine (NTG) iterative random mutagenesis [312]. The resulting mutants were screened in zone-of-inhibition agar plug assays in which the mutant strain 3R-42 produced the largest inhibition zone.…”
Section: Amphotericin Bmentioning
confidence: 99%
“…Previously, several strategies, including overexpression of the pathway-specific regulatory gene, deletion of the global antibiotic downregulator, in situ screening of random mutants, co-culture system, and cultivation with xenobiotics, all failed to improve NPP B1 production (Kim et al, 2018). Recently, the entire cluster containing all six NPP pathway-specific genes in a pSBAC system followed by its re-integration into the P. autotrophica chromosome led to a significant increase in the NPP B1 titer (Han et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro antifungal assay confirmed that the NPP B1, a heptaene version of NPP A1, showed much higher antifungal activity than the tetraene NPP A1 (Kim et al, 2018). Therefore, we tried to generate pharmacokinetically improved heptaene NPP B1 derivative through the engineering of post-PKS modification.…”
Section: Construction Of the Npp B2 Production Strainmentioning
confidence: 99%
See 1 more Smart Citation